KNOWN DISTRIBUTION AND PEST STATUS OF FLUTED SCALE INSECTS (HEMIPTERA MONOPHLEBIDAE ICERYINI) IN SOUTH AMERICA - Kondo, Takumasa; Amalia Ramos-Portilla, Andrea; Peronti, Ana Lucia B. G. [UNESP]; Gullan, Penny J. (Cra-research Centre Agrobiology & Pedology, 2016)
Current information on the known distribution of all 18 species (12 species of Crypticerya Cockerell and 6 species of Icerya Signoret) of fluted scale insects (Hemiptera: Monophlebidae: Iceryini) found in South America is provided. A list of known host plants and natural enemies of these species is given and their pest status in South America is discussed.
Keywords: Crypticerya; Icerya; Monophlebidae; South America; distribution; host plants